(untitled) (Revista Ciência Agronômica, 2021)
Xenogeneic sources are attractive for the development of natural and sustainable biomaterials. The objective of this study was to extract and perform the physicochemical and biological characterization of poultry collagen (G1), nanokeratin (G2) and bioapatite (G3). The test materials were analyzed through SEM, FTIR, TGA, EDS and DRX. The in vivo biocompatibility and biodegradation of the materials were analyzed histopathologically in mice at 1, 3 and 9 weeks post-subcutaneous grafting compared to positive (collagen or commercial bone) and negative (no graft) controls. The obtained data was submitted to intergroup statistical analysis using the ANOVA method with the Tukey-Kramer post-hoc test, and differences were considered signifi cant for p < 0.05. G1 had an irregular fi lamentous microstructure typical of type I collagen, a band spectrum of amide A, I, II and III, common to proteins and compatible with triple helix maintenance, and mass loss after 40.5 °C. G2 had blades of various sizes with rough surface, with bands of amide I, II and reduced amide A and mass loss after 50 °C. G3 presented as white powder, free of organic matter, Ca/P ratio of 1.54, bands of type A and B carbonate substitution, high crystallinity and mass loss after 150 °C. All groups exhibited biocompatibility, with a non-irritating pattern in G1 and slight irritation in G2 and G3, while biodegradation was complete in G1 and G2 and partial in G3. The observed biomimicry, biocompatibility and biodegradation suggest the potential of poultry collagen and nanokeratin as hemostatic agents and bioapatite for bone grafting, requiring future orthotopic effi cacy studies.